Percepção acerca do consumo de sal e o hábito de substituir refeições por lanches em brasileiros com doença renal crônica: pesquisa nacional de saúde, 2019 - Vasconcelos, Mayra Solange Lopes de (2023)
INTRODUCTION: Chronic kidney disease (CKD) is one of the diseases that most contribute to the increase in mortality from chronic noncommunicable diseases (NCDs) in Brazil and worldwide. Eating habits that predispose to higher consumption of sodium, saturated fats and chemical additives have been associated with worse health prognoses, especially for those with CKD, contributing to its worse progression and higher mortality. OBJECTIVE: To investigate the relationship between CKD and the perception of salt consumption and the habit of replacing meals with quick snacks and the presence of changes in the effect of gender and age on these associations. METHODS: Cross-sectional study with data from 90,717 participants of the National Health Survey (PNS), 2019 edition. The outcomes analyzed were the perception of salt intake (adequate, very high, high, low and very low) and the habit of replacing meals for quick snacks such as sandwiches, snacks, pizza and hot dogs (5 < and > 5 times a week), while having CKD (No and Yes) was investigated as an exposure of interest. The description of variables was performed using absolute and relative frequencies, and their respective 95% confidence intervals (95%CI). The prevalences (95%CI) of the classifications on the perception of salt consumption and the frequency of replacing meals with quick snacks were described for individuals with CKD. The magnitudes of the associations between CKD and the perception of salt consumption, as well as the frequency with which meals are replaced by quick snacks, were estimated using logistic and multinomial regression when necessary (Model 1) and later adjusted for sex, age (Model 2), schooling and macro-region of Brazil (Model 3). Interaction terms (CKD*age and CKD*sex) were included in the models considering the total population after complete adjustment (Model 3) to verify the change in the effect of sex and age on these relationships. Analyzes were performed using the Stata 17.0 statistical program. RESULTS: The majority of the study population consisted of women (52.94%), aged less than 40 years (49.09%), residents of the southeastern region of the country (43.10%), with incomplete primary education (34.32% ). 1.41% reported the diagnosis of CKD and of these 3.97% replace meals with snacks 5 or more times a week, and 11.19% perceive their salt intake as high/very high and 37.31% as low/ very low. After removing the effect of possible confounders (gender, age, education and macroregion of Brazil), having CKD was associated with a 32% (95%CI 1.04 - 1.66) greater chance of perceiving salt intake as low and 137% (95%CI 1.68 - 3.33) higher of having a perception of salt intake as very low, compared to those without the disease. With regard to the habit of replacing meals with quick snacks, having the disease was associated with a 120% (95%CI 1.68 - 3.33) greater chance of performing this replacement five or more times a week compared to those without the disease. We did not observe a change in the effect of gender and age on the presence of CKD and their perception of salt consumption and a higher frequency of replacing meals with quick snacks. CONCLUSION: This study suggests that salt consumption may be higher than the individual's self-perception and that the frequent habit of replacing main meals with snacks containing ultra-processed foods may indicate the need for greater attention to diet quality, especially in patients with CKD , since the excessive consumption of ultra-processed foods could have an impact on worse prognosis related to the disease.